2023
DOI: 10.1039/d3nj00330b
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of spinous gold nanoparticles and their use for surface-enhanced Raman scattering (SERS) detection of the antibiotic sulfathiazole

Abstract: Sulfathiazole is an antibiotic used to prevent diseases and promote animal growth, which may pose human health risks due to excessive consumption. Herein, we prepared a nano substrate for trace...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…SERS is a very sensitive technique with a great potential for the detection of trace analytes [62,63]. In fact, the SERS technique enhances the weak Raman signals of the probe molecules thanks to the hot spot generated from a nano-metallic substrate at close distance [64].…”
Section: Sers-based Mnps Detectionmentioning
confidence: 99%
“…SERS is a very sensitive technique with a great potential for the detection of trace analytes [62,63]. In fact, the SERS technique enhances the weak Raman signals of the probe molecules thanks to the hot spot generated from a nano-metallic substrate at close distance [64].…”
Section: Sers-based Mnps Detectionmentioning
confidence: 99%
“…2 For example, Nguyen et al 3 recently evaluated adsorption behavior and SERS spectra of 5fluorouracil on small gold clusters involving 6, 8, and 20 Au atoms employing density functional theory (DFT) at the PBE-D3/cc-pVDZ-PP level for Au and the PBE-D3/cc-pVTZ level for nonmetal atoms. Vo et al 4 analyzed SERS properties of sulfathiazole antibiotic using DFT calculations on the Au 20 pyramidal cluster model. Interestingly, Dao et al 5 investigated the SERS spectra of 2,4,5-trichlorophenoxyacetic acid (2,4,5-T) adsorbed on silver nanoparticles by employing both the metallic cluster model (i.e., Ag n with n = 4, 8, 20) and periodic slab one.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Nguyen et al recently evaluated adsorption behavior and SERS spectra of 5-fluorouracil on small gold clusters involving 6, 8, and 20 Au atoms employing density functional theory (DFT) at the PBE-D3/cc-pVDZ-PP level for Au and the PBE-D3/cc-pVTZ level for nonmetal atoms. Vo et al . analyzed SERS properties of sulfathiazole antibiotic using DFT calculations on the Au 20 pyramidal cluster model.…”
Section: Introductionmentioning
confidence: 99%
“…They display a great potential for diagnosis and personalized treatment either as a substrate for SERS investigations [17][18][19] or by themselves, considering the fact that they can improve antimicrobial activity [20]. A lot of antibiotics such as levofloxacin, tetracycline, benzylpenicillin [11], sulfathiazole [21,22], quinolones [23], ciprofloxacin [24], and many others [17] have been studied through the SERS method. It has also been shown that antibiotic-functionalized gold nanoparticles can detect β-lactamase and be used as a useful tool in combating antimicrobial resistance [25].…”
Section: Introductionmentioning
confidence: 99%